2004
DOI: 10.1097/00001756-200409150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Passive music listening spontaneously engages limbic and paralimbic systems

Abstract: In this PET study, non-musicians passively listened to unfamiliar instrumental music revealed afterward to elicit strongly pleasant feelings. Activations were observed in the subcallosal cingulate gyrus, prefrontal anterior cingulate, retrosplenial cortex, hippocampus, anterior insula, and nucleus accumbens. This is the first observation of spontaneous responses in such limbic and paralimbic areas during passive listening to unfamiliar although liked music. Activations were also seen in primary auditory, secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
243
2
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(274 citation statements)
references
References 18 publications
20
243
2
9
Order By: Relevance
“…Surprisingly, however, activity in classical emotion-processing regions, such as the insula, the orbitofrontal cortex, and the anterior cingulate cortex (Adolphs, 2002;Keysers, Kaas, & Gazzola, 2010;Petrini, et al, 2011), has so far been reported only for tasks of dance observation (Cross, Kirsch, Ticini, & Schuetz-Bosbach, 2011;Jang & Pollick, 2011). Activity in such regions has not been found to be especially relevant in tasks of aesthetic appreciation of dance movements, which may be puzzling considering the rather large amount of empirical and theoretical work linking emotional and affective processes with art appreciation (Leder, Belke, Oeberst, & Augustin, 2004;Aharon, Etcoff, Ariely, Chabris, O'Connor, Breiter, 2001;Blood & Zatorre, 2001;Brown, Martinez, & Parsons, 2004;Vartanian & Goel, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, however, activity in classical emotion-processing regions, such as the insula, the orbitofrontal cortex, and the anterior cingulate cortex (Adolphs, 2002;Keysers, Kaas, & Gazzola, 2010;Petrini, et al, 2011), has so far been reported only for tasks of dance observation (Cross, Kirsch, Ticini, & Schuetz-Bosbach, 2011;Jang & Pollick, 2011). Activity in such regions has not been found to be especially relevant in tasks of aesthetic appreciation of dance movements, which may be puzzling considering the rather large amount of empirical and theoretical work linking emotional and affective processes with art appreciation (Leder, Belke, Oeberst, & Augustin, 2004;Aharon, Etcoff, Ariely, Chabris, O'Connor, Breiter, 2001;Blood & Zatorre, 2001;Brown, Martinez, & Parsons, 2004;Vartanian & Goel, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Strong empirical evidence has been slow to emerge, although an increasing number of studies have documented effects of music on various emotion components: feeling (Pike, 1972), emotional expression (Witvliet & Vrana, 2007), psychophysiology (Krumhansl, 1997), brain activation (Brown, Martinez, & Parsons, 2004), and behavior tendency (Fried & Berkowitz, 1979).…”
mentioning
confidence: 99%
“…The release hallucinations concept is based on West's perceptive theory, whose main hypothesis is that blindness and deafness interrupt external sensorial stimuli necessary to inhibit brain memory evocation. 5,7,22,23 This phenomenon will release previously stored perceptions and visual or auditory memories. 3,4 Release musical hallucinations occur mainly in the elderly with hearing deficiencies, mainly while awakening.…”
Section: Discussionmentioning
confidence: 99%